A Dynamical Stiffness Evaluation Model for a Ring-Shaped Superconductor Magnetic Bearing System - Sivrioglu, Selim; Basaran, Sinan (IEEE-Inst Electrical Electronics Engineers Inc, 2015)
In this paper, a rotor-permanent magnet inside a ring-shaped superconductor magnetic bearing system is modeled and simulated using a dynamic stiffness approach. Analytical expressions of the stiffness effects are defined on the basis of a magnetic potential obtained with a frozen-image concept. For engineering applications, the rotor dynamics must be considered with the effective stiffness of the ring-shaped superconducting magnetic bearing. In the proposed model, the variation of the stiffness and the dynamics of the rotor are analyzed for some initial angular and translational movements.
Keywords: Frozen-image concept; stiffness simulation; superconducting magnetic bearing